Analisis Perbandingan Waktu Dan Biaya Bekisting Metode Konvensional Dengan Sistem Table Formwork Pada Pembangunan Gedung At-Taawun Universitas Muhammadiyah Surabaya - Novianti Dwi Rahayu; Mohamad Khoiri; Ragil Purnamasari (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2025)
The At-Taawun Building, being constructed by Muhammadiyah University of Surabaya, is classified as a high-rise structure due to its 19 tower levels and 1 basement floor. The formwork for this project is based on the convenstional formwork system. Research findings indicate that the multiplex use maximum cycle will impact the fabrication and dismantling process, resulting in a longer times for the conventional method compared to the other approaches. In contrast, the phenolic film cycle and the formwork table's module shape allow for faster construction and disassembly. Based on the results of the analysis, reveal that completing the task with the table formwork approach would take 130 days, compared to 155 days with conventional methods. According to calculations, the conventional methode's implementation total cost comes as much as IDR21.598.777.449,93, while the total cost of table formwork method is IDR22.610.784.905,70